Temporal metabolic reprogramming in DSS-induced colitis identifies purine metabolism and trigonelline as novel therapeutic targets - Zhang, Qi; Wang, Jianguo; Zhang, Long; Song, Kangjie; Sun, Xiaoming; Zhang, Yaming; Liu, Fubao (Frontiers in Pharmacology, 2025)
BackgroundInflammatory bowel disease (IBD) is a multifactorial disorder characterized by aberrant immune activation and metabolic dysregulation. Despite significant advances in understanding immune mechanisms, the temporal dynamics of metabolic alterations during intestinal inflammation and their therapeutic implications remain poorly defined.MethodsTo investigate metabolic reprogramming during colitis progression, we conducted time-resolved metabolomic profiling of the colon, mesenteric lymph nodes (MLNs), and serum in a dextran sulfate sodium (DSS)-induced murine colitis model at days 1, 3, 5, and 7 post-induction. Targeted and untargeted metabolomic analyses were integrated with pathological and immunological assessments. To assess therapeutic relevance, DSS-treated mice were administered either trigonelline, a metabolite identified in serum, or mycophenolic acid (MPA), a purine metabolism inhibitor, separately. Metabolomic profiling revealed a progressive activation of purine metabolism in colonic tissues and MLNs, correlating with enhanced immune-inflammatory responses.ResultsTrigonelline was identified as a serum biomarker positively associated with disease severity. Therapeutic treatment with either trigonelline or MPA significantly alleviated histopathological damage, reduced inflammatory cell infiltration in both the colon and MLNs, and restored the Th17/Treg cell balance. Mechanistic studies indicated that trigonelline and MPA individually suppress pro-inflammatory signaling pathways while promoting regulatory immune responses.ConclusionThis study provides a comprehensive temporal map of metabolic reprogramming during colitis progression and identifies purine metabolism and trigonelline as novel therapeutic targets. These findings highlight the translational potential of multi-organ metabolomic approaches in elucidating disease mechanisms and guiding precision treatment strategies for IBD and related inflammatory conditions.